Efeitos do uso de glicocorticoides sobre o metabolismo da glicose em ratos: estudo comparativo entre dexametasona e prednisona - MELO, Danylo Noleto de Sousa (2016)
Synthetic glucocorticoids (GCs) induce several adverse effects when administered in high doses and/or prolonged, as peripheral insulin resistance, glucose intolerance, and alterations in lipid metabolism, especially hypertriglyceridemia. There are few studies on the metabolic impact caused by long-term treatments with different synthetic GCs, especially with prednisone, GC of intermediate action and first choice in its pharmacologic class. Therefore, we seek to verify the metabolic alterations caused by sub chronic treatment with prednisone in rats and compare them with existing and in acute model of insulin resistance induced by dexamethasone effects. For this, Wistar rats with of 90 days were treated with dexamethasone (D5) (1 mg/kg, i.p.) for 5 consecutive days and, its controls (C5) with saline, and Wistar rats of 60 days old were treated with prednisone (80 mg/kg, orally) for 15 days (P15) and 30 days (P30) consecutive and their respective controls (C15 and C30), received vehicle solution. The D5 results a decreased body weight (12.3%) and lower weight of retroperitoneal fat (38%), increased serum fasting glucose (12%) and fed (30%), insulin (80%) and triglycerides (339%) (p <0.05). Total fat and triglycerides liver were 29% and 52% higher in rats D5, compared to the C5 rats (p <0.05). The P15 rats had increased weight 61% less, reduction of retroperitoneal fat (29%) and increased plasma triglyceride concentrations (60%) compared to the C15 rats (p <0.05). As long as P30 rats had increased weight 44% less, reduction of retroperitoneal fat (25%) and increased serum triglycerides (78%) and liver total fat (26%) compared to the C30 rats (p <0,05). In vivo tests revealed the presence of impaired glucose tolerance (oGTT) in rats D5 and P30, and reduced insulin sensitivity (ipITT, HOMA, TYG) in D5 animals (p <0.05). Ex vivo test showed greater sensitivity in the pancreatic islets front glucose only in D5 rats. In conclusion, the sub chronic administration of prednisone promoted finer metabolic changes in glucose homeostasis, compared to acute administration of dexamethasone, suggesting the preferential use of prednisone when it is intended to minimize the adverse metabolic effects associated with the use of GCs.